Improving access to appropriate case management for common childhood illnesses in hard-to-reach areas of Abia State, Nigeria - Chinwoke Isiguzo; Samantha Herrera; Joy Ufere; Ugo Enebeli; Chukwuemeka Oluoha; Jennifer Anyanti; Debra Prosnitz (Inishmore Laser Scientific Publishing Ltd, 2019)
# Background Studies have demonstrated that trained community health workers can improve access to quality health services for under five children. Under the World Health Organization's Rapid Access Expansion Progamme, integrated community case management of childhood illnesses (iCCM) was introduced in Abia and Niger States, Nigeria in 2013. The objective of the program was to increase the number of children 2-59 months receiving quality life-saving treatment for malaria, pneumonia and diarrhoea by extending case management through community-oriented resource persons (CORPs). We present findings from household surveys comparing baseline and endline data to assess changes in sick child care-seeking, assessment, and treatment coverage provided over the project period in Abia State. # Methods A baseline household survey was conducted in May 2014 and an endline survey in February 2017. The surveys used multi-stage cluster sampling of primary caregivers of children aged 2-59 months who had been recently sick with diarrhoea, fever, or cough with difficult breathing. # Results Care-seeking from an appropriate provider improved significantly from 69% at baseline to 77% at endline (*P*\<0.01). At baseline, patent and proprietary medicine vendors (PPMVs) (55%) and health centers (34%) were the main providers of care for iCCM services; by endline, CORPs became the main source (48%), followed by PPMVs (36%) and health centers (25%). # Conclusions Overall, the findings demonstrate improvements in care-seeking. Care-seeking practices shifted over the course of the project, with more caregivers seeking care from CORPs by the end of the project. The findings suggest that scaling up iCCM in Nigeria may improve access to appropriate treatment for under five children living in hard-to-reach areas.